Prevalence and Determinants of Gastrointestinal Manifestations in Patients with Selected Rheumatologic Diseases - Asfuroğlu Kalkan, Emra; Kalkan, Çağdaş; Barutcu, Sezgin; Küçükşahin, Orhan; Güçbey, Özge; Köseoğlu, Tankut; Şendil, Ateş; Hamamcı, Mevlüt; Özaslan, Ersan; Ateş, İhsan; Altıparmak, Emin; Soykan, İrfan (Turkish Journal of Gastroenterology, 2022)
Background: Many rheumatic diseases may cause gastrointestinal manifestations. The goal of this study was to analyze the prevalence and predictors of gastrointestinal involvement in patients with rheumatic disorders.Methods: A retrospective chart review was performed for patients with systemic lupus erythematosus, rheumatoid arthritis, and sys- temic sclerosis who have consulted due to gastrointestinal symptoms. The relationship between clinical symptoms, gastroscopic/colo- noscopic findings, and histopathological results with current drugs and disease duration was evaluated.Results: A total of 364 patients with rheumatic disorders and 740 people as control group were included in the study. Abdominal bloating followed by abdominal pain, regurgitation, and heartburn were reported as the main complaints by more than half of the patients. Most of the patients had gastric mucosal changes expressed as Lanza score, and the presence of major polypharmacy was the most important factor affecting Lanza score (odds ratio: 10, 95% CI: 1.882-54.111, P < .007) followed by disease duration (odds ratio: 1.559, 95% CI: 1.369-1.775, P < .001) and age (odds ratio: 1.069, 95% CI: 1.030-1.109, P < .001). In general, approximately 30% of the patients were posi- tive for Helicobacter pylori infection and 35% showed intestinal metaplasia in histopathological examination. Most of the colonoscopic findings were associated with colonic polyps (n = 81). In multivariate analysis, disease duration was the only factor that affected the pres- ence of colonic lesions (Area Under the Receiver Operating Characteristic (ROC) Curve (AUROC): 0.871, 95% CI: 0.824-0.918, P < .001). Conclusion: Patients with rheumatologic diseases frequently have gastrointestinal manifestations. The most encountered gastrointes- tinal symptom was abdominal bloating, followed by abdominal pain. Being aware of gastrointestinal manifestations and their determi- nants may help physicians manage and follow patients with rheumatologic disorders.